Vipassana 'Dhammasaya' Changes Social Behaviour of Inmates - Maharjan, Upesh (Shahid Kirti Multidisciplinary Journal, 2025)
Vipassana Meditation is a technique discovered by Buddha more than 2500 years ago has been practiced in many countries in the world. This is a non-denominational scientific technique of self-transformation through self-observation in society. Several studies around the world have revealed that the positive effects of this Meditation. The descriptive qualitative research method has been used to explore the social behavioral changes of inmates meditating on Nakkhu Vipassana Centre 'Dhammasaya'. Out of 43 inmates, 9 inmates have been purposively selected as sample to take research data. Also for key informant interview, the Deputy prime minister, three vipassana trainers, one jailer and two police personnel have been selected for primary data. The qualitative data from 16 samples have been collected and thematically analysized. Empirical results have revealed that it has assessed to develop positive and optimistic attitude; reduce anger, irritation and anxiety; make self-correction of behaviour; improve physical and mental health and purify their mind and character in 'Dhammasaya'. Thus the study has revealed that Vipassana meditation in it is more effective for social reintegration and jail reform in Nepal.